Reflections on the early Christian history of religion = Erwägungen zur frühchristlichen religionsgeschichte - Breytenbach, Cilliers, 1954-; Frey, Jörg. (Ancient Judaism and Early Christianity, 2012)
Reflections on the Early Christian History of Religion documents the results of two recent workshops on Martin Hengel's and Maria Schwemer's first volume of first volume of Geschichte des frühen Christentums ( Jesus und das Judentum [title of volume 1], Tübingen 2007) and Larry Hurtado's Lord Jesus Christ: Devotion to Jesus in Earliest Christianity (Grand Rapids 2003). The contributors, including Hengel himself, focus on problems and possibilities of studying and presenting Christian religion in Roman Antiquity. They discuss distinctive features of these two remarkable publications and some material aspects that illustrate the relationship between the historical study of early Christian religion, religious studies in general and New Testament studies in particular. Mit den Erwägungen zur frühchristlichen Religionsgeschichte liegen die Ergebnisse zweier Fachtagungen vor, die sich mit dem ersten Band der Geschichte des frühen Christentums von Martin Hengel und Maria Schwemer ( Jesus und das Judentum , Tübingen 2007) und Larry Hurtados Lord Jesus Christ: Devotion to Jesus in Earliest Christianity (Grand Rapids 2003) beschäftigt haben. Die Beiträge, u.a. von Hengel selbst, diskutieren Probleme und Möglichkeiten der Erforschung und Darstellung christlicher Religion in der römischen Antike. Sie setzen sich mit den Zugangsweisen dieser beiden Bücher auseinander und zeigen an verschiedenen Sachfragen die Bezüge, die sich bei der historischen Erforschung der frühchristlichen Religion zwischen Geschichtswissenschaft, Religionswissenschaft und Neutestamentlicher Wissenschaft ergeben.